Clinical and demographic factors associated with pediatric difficult intravenous access in the operating room. Issue 7 (23rd March 2022) - Ballard, Heather A.; Hajduk, John; Cheon, Eric C.; King, Michael R.; Barsuk, Jeffrey H.
Abstract: Background: Pediatric intravenous catheter insertion can be difficult in the operating room due to the technical challenges of small diameter vessels and the need to rapidly gain intravenous access in anesthetized children. Few studies have examined factors associated with difficult vascular access in the operating room, especially accounting for the increased possibility to use ultrasound guidance. Aims: The primary aim of the study was to identify factors associated with pediatric difficult vascular access in the operating room. Our primary hypothesis was that Black race, Hispanic ethnicity, and ultrasound use would be associated with pediatric difficult vascular access. Methods: We performed a retrospective analysis of prospectively collected data from a cohort of pediatric patients who had intravenous catheters inserted in the operating room at an academic tertiary care children's hospital from March 2020 to February 2021. We measured associations among patients who were labeled as having difficult vascular access (>2 attempts at access) with demographic, clinical, and hospital factors. Results: 12 728 intravenous catheter insertions were analyzed. Multivariable analysis showed significantly higher odds of difficult vascular access with Black non‐Hispanic race (1.43, 95% CI: 1.06–1.93, p = .018), younger age (0.93, 95% CI: 0.89–0.98, p = .005), overweight (1.41, 95% CI: 1.04–1.90, p = .025) and obese body mass index (1.56, 95% 95% CI: 1.12–2.17, p = .008), and American Society of Anesthesiologists physical status III (1.54, 95% CI:1.11–2.13, p = .01). The attending anesthesiologist compared to all other practitioners (certified registered nurse anesthetist: (0.41, 95% CI: 0.31–0.56, p < .001, registered nurse: 0.25, 95% CI: 0.13–0.48, p < .001, trainee: 0.21, 95% CI: 0.17–0.28, p ‐value <.001 with attending as reference variable) and ultrasound use (2.61, 95% CI: 1.85–3.69, p < .001) were associated with successful intravenous catheter placement. Conclusions: Black non‐Hispanic race/ethnicity, younger age, obese/overweight body mass index, American Society of Anesthesiologists physical status III, and ultrasound were all associated with pediatric difficult vascular access in the operating room.